The STAT5 transcription factor in B-cells of patients with chronic lymphocytic leukemia - Matvieieva, A.S.; Kovalevska, L.M.; Ivanivska, T.S.; Klein, E.; Kashuba, E.V. (Вiopolymers and Cell, 2019)
Aim. To find out the cause of inhibition of the IL2-STAT5 signaling pathway in chronic lymphocytic leukemia (CLL) cells. Methods.CLL cells were isolated from peripheral blood, using gradient centrifugation on a ficoll-verografin mixture. Expression of the STAT1-6 genes at the mRNA level was analyzed, using the Oncomine database. Expression, phosphorylation status and cellular localization of the STAT5 protein were studied by fluorescence microscopy, using specific antibodies. Results.Unlike B-cells of healthy donors, expression of the STAT5A protein was low in the patient CLL cells. As we have previously shown, the IL-2-STAT5 (JAK-STAT5) signaling pathway is inhibited in CLL cells. Now we demonstrated a low level of phosphorylation of the STAT5 protein, or a complete lack of phosphorylation in CLL cells. The STAT5A protein shows cytoplasmic localization, indicating the absence of complexes in the nucleus that activate/repress transcription of the STAT5-dependent genes. Conclusions. Inhibition of the IL-2-STAT5 pathway in CLL cells is caused by a lack of the STAT5 proteins phosphorylation and/or the absence of the active STAT5A transcription complexes in the nucleus of CLL cells.